204 Therapeutic plasma exchange for neurological disorders: the experience of a tertiary neuroscience centre. Issue 12 (14th November 2019) - Parker, Sarah; Das, Joyutpal; Hewamadduma, Channa
Abstract : The role of Therapeutic plasma exchange (TPE) in immune-mediated neurologic disorders is expanding. Our experience with TPE at a tertiary neuroscience centre is reported. Medical records of all patients who received TPE between 2013 and 2018 at Sheffield Teaching Hospitals NHS Foundation Trust were reviewed. The procedure involved the removal of 1–1.5 plasma volumes and replacement with isotonic 4.5% human albumin solution. A typical cycle consisted of 5–7 procedures within 14 days. A total of 66 patients received 478 TPE procedures over 76 therapeutic cycles. TPE was performed for 16 neurological indications including multiple sclerosis (34.8%), Guillain-Barre syndrome (13.6%) and neuromyelitis optica spectrum disorder (9.1%). 78.8% of patients received TPE for category I or II indications according to The American Society for Apheresis (ASFA) guidelines. 73.8% of patients in our cohort demonstrated neurological improvement following TPE. 21.2% of patients responded to TPE administered for indications outside the ASFA guidelines. There was no treatment related mortality. Complications associated with TPE included bacteraemia, pulmonary embolism, deep vein thrombosis and bacterial endocarditis. Our data suggests that TPE was associated with favourable outcomes. Further studies are required to assess the efficacy of TPE in those conditions for which there is currently little evidence.